2011
DOI: 10.1007/s13524-011-0030-7
|View full text |Cite
|
Sign up to set email alerts
|

Estimating a Dynamic Model of Sex Selection in China

Abstract: High ratios of males to females in China, which have historically concerned researchers (Sen 1990), have increased in the wake of China's one-child policy, which began in 1979. Chinese policymakers are currently attempting to correct the imbalance in the sex ratio through initiatives that provide financial compensation to parents with daughters. Other scholars have advocated a relaxation of the one-child policy to allow more parents to have a son without engaging in sex selection. In this article, I present a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(57 citation statements)
references
References 30 publications
2
55
0
Order By: Relevance
“…Sen (2003) concludes that in the 2000s, about 100 million women were missing worldwide. In China alone, for instance, the sex ratio at birth rose from a biologically normal range of 1.03-1.06 to 1.11 in 1990, and further increased to 1.20 in 2000, resulting in 33 million excess men under the age of 20 (Ebenstein, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sen (2003) concludes that in the 2000s, about 100 million women were missing worldwide. In China alone, for instance, the sex ratio at birth rose from a biologically normal range of 1.03-1.06 to 1.11 in 1990, and further increased to 1.20 in 2000, resulting in 33 million excess men under the age of 20 (Ebenstein, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Alesina, Giuliano, and Nunn (2013) explore historical origins of cross-cultural differences in the role of women in society, and find that traditional agricultural practices, such as plowing, influenced the historical gender division of labor and the evolution of gender norms. 3 Our paper borrows insights from behavioral economics, and presents the first at-1 For the long-run socioeconomic consequences of gender imbalance, see Rao (1993), Angrist (2002), Chiappori, Fortin, andLacroix (2002), Das Gupta (2005), Ebenstein (2010Ebenstein ( , 2011, Wei and Zhang (2011), Bethmann and Kvasnicka (2012), Das Gupta, Ebenstein, and Sharygin (2013), Edlund, Li, Yi, and Zhang (2013), and Hu and Schlosser (2015). 2 Leung (1988,1991) proposes the econometric method to detect son preference using fertility data.…”
mentioning
confidence: 99%
“…Unlike developed markets, such as the U.S. or Europe, discrimination against females is more severe and explicit in China due to social norms and weaker legal protection for women (OECD 2012;World Bank 2013). Moreover, compared to developed economies, there are greater variations in sex discrimination across different areas within China (Ebenstein 2011;Wei and Zhang 2011a), which allows us to implement withincountry comparative studies. In addition, as of 2014, China is the second largest economy in the world; thus, understanding how corporate managers are selected in China is economically meaningful from a global perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In the Republic of Korea simulations suggested that introduction of sex selection changed family size little, but did result in abortions of female fetuses equal to about five percent of actual female births (Park and Cho, 1995). For China allowing a three-child policy has been predicted to increase the fertility rate by 35 percent, but also reduce the number of girls aborted by 56 percent (Ebenstein, 2011). 6 Most of the sex selection in China is due to parents with low levels of education (Ebenstein, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…For China allowing a three-child policy has been predicted to increase the fertility rate by 35 percent, but also reduce the number of girls aborted by 56 percent (Ebenstein, 2011). 6 Most of the sex selection in China is due to parents with low levels of education (Ebenstein, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%